2006
DOI: 10.1007/11940128_56
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Scheme for Lowest Outdegree Orientation and Graph Density Measures

Abstract: Abstract. We deal with the problem of finding such an orientation of a given graph that the largest number of edges leaving a vertex (called the outdegree of the orientation) is small. For any ε ∈ (0, 1) we show anÕ(|E(G)|/ε) time algorithm 3 which finds an orientation of an input graph G with outdegree at most (1 + ε)d * , where d * is the maximum density of a subgraph of G. It is known that the optimal value of orientation outdegree is d * . Our algorithm has applications in constructing labeling schemes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…We could prove Lemma 5 directly with a simple counting argument on the indegrees of nodes in R k (see Appendix A) or by using a network flow construction similar to Goldberg's and the max flow-min cut theorem [18]. The upper bound given in Lemma 6 may be proven directly by using a counting argument for the indegrees of vertices in an egalitarian orientation of the densest subnetwork (see Appendix A) or by using the relationship between the density of the maximum density subgraph and the psuedoarboricity [24].…”
Section: Density and The Density Decompositionmentioning
confidence: 99%
“…We could prove Lemma 5 directly with a simple counting argument on the indegrees of nodes in R k (see Appendix A) or by using a network flow construction similar to Goldberg's and the max flow-min cut theorem [18]. The upper bound given in Lemma 6 may be proven directly by using a counting argument for the indegrees of vertices in an egalitarian orientation of the densest subnetwork (see Appendix A) or by using the relationship between the density of the maximum density subgraph and the psuedoarboricity [24].…”
Section: Density and The Density Decompositionmentioning
confidence: 99%
“…[11] for some relations between classes of sparse graphs). We show that any n-vertex twinless graph of arboricity c contains an induced matching of size Ω( 1 c n 1/c ).…”
Section: E(g[j])| |J|mentioning
confidence: 99%
“…Edge Orientation Problem. Since Venkateswaran [27] introduced the problem, (centralized) polynomial-time algorithms are known to give optimal solutions for unweighted graphs [3], [21], [27]. However, a series of works [2], [3] showed that the weighted version is NP-hard even when all edge weights belong to the set {1, k}, where k is any fixed integer greater than 1; on the other hand, for integer edge weights, (2 − 1 k )-approximation can be achieved, where k is the maximum weight.…”
Section: Min-maxmentioning
confidence: 99%